Ingredients used for marinating the fish - Mumbai Archive Project Team (Jio Institute, 2024)
Turmeric powder, red chilli powder, salt, ginger-garlic paste, and occasionally a small amount of vinegar or lemon juice are common ingredients used in the marinade. To allow the spices to seep into the fish, deep cuts are made on the sides. Marinating fish allows for an even distribution of seasoning throughout the meat, ensuring that every bite is well-seasoned and flavourful.